P237 Enzyme complexes of alcohol metabolism protect against liver injury in animal models fed acute alcohol and anti-HIV drugs. (14th July 2019) - Ji, Cheng
Abstract : Background: A significant portion of AIDS patients under anti-HIV therapies consume or abuse alcohol, which causes liver injuries. This study was to evaluate effects of eliminating blood alcohol on anti-HIV drugs and alcohol-induced liver injuries through utilizing nanoparticles of enzyme complexes of alcohol metabolism that were developed previously. Methods: The enzyme nanoparticles were intravenously injected into mouse models of acute alcohol binge or chronic alcohol and antiviral feeding in the presence of antivirals (ritonavir-boosted lopinavir). Parameters for liver pathologies were examined. Results: In the acute model, the enzyme nanoparticles significantly reduced the blood alcohol concentration (BAC) within four hours compared to control. No significant effects of the anti-HIV drugs on BAC were observed in the acute alcohol binge model. Plasma alanine aminotransferase (ALT) and expression of liver TNFα were both significantly increased in the alcohol fed mice, which were normalized by the enzyme nanoparticles. In the presence of the antivirals, ALT was partially reduced by the enzyme nanoparticles. In the chronic alcohol feeding, alcohol induced inflammation, fatty liver and increase of ALT, which were deteriorated by the antivirals. the enzyme nanoparticles slightly reduced BAC, ALT and expression of inflammation markers of TNFα, F4/80 and IL-6 and lipogenic factors of ACC, LXRa and SREBP1. In addition, the anti-HIV drugs potentiated alcohol induced expression of cellular organelle stress markers of CHOP, sXBP-1, ATF6 and GCP60, which were not reduced by the application of the enzyme complexes. Conclusion: Eliminating blood alcohol by the enzyme nanoparticles protects the liver against acute alcohol-induced liver injuries, and the protection is much less effective under chronic alcohol feeding or combination of alcohol and antiviral use due to severe cellular stresses in the liver. Disclosure: No significant relationships.